2016
DOI: 10.5665/sleep.6228
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Twin and Sibling Study of Associations between Insomnia and Depression Symptoms in Young Adults

Abstract: Study Objectives: To estimate genetic and environmental influences on the associations between insomnia and depression symptoms concurrently and longitudinally. Methods: Behavioral genetic analyses were conducted on data from the British longitudinal G1219 twin/sibling study. One thousand five hundred fiftysix twins and siblings participated at Time 1 (mean age = 20.3 years, SD = 1.76). Eight hundred sixty-two participated at Time 2 (mean age = 25.2 years, SD = 1.73 years). Participants completed the Insomnia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…The total scale score was calculated by summing the responses and ranges from 0 to 24, with higher scores meaning more severe insomnia symptoms. Cronbach's alpha for the ISQ in the current sample was 0.87 (as reported in previous studies; Gregory et al, 2016;Schneider et al, in press).…”
Section: Insomnia Symptomssupporting
confidence: 83%
“…The total scale score was calculated by summing the responses and ranges from 0 to 24, with higher scores meaning more severe insomnia symptoms. Cronbach's alpha for the ISQ in the current sample was 0.87 (as reported in previous studies; Gregory et al, 2016;Schneider et al, in press).…”
Section: Insomnia Symptomssupporting
confidence: 83%
“…23,24,30,71 For insomnia we found a similar F o r R e v i e w O n l y 14 heritability estimate, and our results are also similar to those from studies of young and middle-aged adults. 26,29 For all measures of internalising symptoms, higher correlations were found between MZ as compared to DZ twins. Our results showed that genetic influences accounted for a significant proportion of the variance in these phenotypes.…”
Section: Genetic and Environmental Influences On Poor Sleep Qualitymentioning
confidence: 97%
“…[26][27][28][29] Regarding depression and anxiety, approximately 30-50% of the variance is typically explained by genetic factors. 9,[29][30][31][32] Studies examining the overlap between these variables have found that there is a substantial (sometimes complete) genetic overlap, with genetic correlations all above .5. 9,29,30,33 Adolescence is a period of great change for sleep.…”
Section: Genetics Of Sleep Quality Insomnia Depression and Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicate that the association of suicides with hypnotic use cannot be entirely attributed to confounders with reverse causality, since the association of hypnotic usage with depression is known to be largely caused by the hypnotics 34 . Since the genetic influences promoting insomnia and depression appear highly correlated 103 , the associations both of depression and insomnia with mortality may be mediated through hypnotic drug consumption.…”
Section: Hypnotics Increase Incidence Of Clinical Depressionmentioning
confidence: 99%